[PP.26.03] CLINICAL SIGNIFICANCE OF MISSLEADING OFFICE BLOOD PRESSURE MEASUREMENTS IN TREATMENT OF HYPERTENSION. (September 2017) - Dapic, K.; Domislovic, V.; Vrkic, T. Zeljkovic; Josipovic, J.; Premuzic, V.; Pocanic, D.; Likic, R.; Laganovic, M.; Jelakovic, A.; Dika, Z.; Kos, J.; Karanovic, S.; et al.
Abstract : Objective: According to the EHUH study control of hypertension based only on office blood pressure (BP) measurements is achieved in less than 25% of treated hypertensives in general Croatian population. Our aim in this paper was to analyze control of BP using both office and ABPM devices in treated hypertensive patients enrolled in the Croatian registry of ABPM. Design and method: Data of subjects from registry with more than 70% successful ABPM readings were analyzed. Office BP was measured by Omron M6 device following ESH/ESC guidelines, and ABPM data were obtained using SpaceLabs or Microlife machines. Office controlled hypertension was defined as BP less than 140/90 mmHg, and ABPM control as average daytime BP less than 135/85 mmHg. White coat hypertension (WCH) was defined as office BP >140/90 mmHg and daytime ABPM < 135/85 mmHg while masked uncontrolled hypertension (MUCH) as office BP < 140/90 mmHg and daytime ABPM > 135/85 mmHg, true BP control was defined as office BP < 140/90 mmHg and daytime ABPM < 135/85 mmHg. Results: Significant differences between office BP and daytime and 24-hour ABPM values were obtained (13.2/8 mmHg and 16.1/10.6 mmHg, respectively <0.001). True BP control was found in 19.8%, while WCH and MUCH were observed in 26.6% and 9.9%, respectively. There were significantly more men and subjects which consume alcohol and less diabetics in MUCH group, while in WCH group there were more women, diabetics, non-smokers and alcohol abstainers. Prevalence of nondippers, dippers, extreme dippers and reverse dippers was 26.7%, 44.5%, 13.6%, 15.1%, respectively. Reverse dipping and non dipping pattern were associated with older age, while extreme dipping pattern with younger age. Conclusions: Data from Croatian registry revealed that 36.5% hypertensive patients were inappropriately treated when BP control was judged and estimated only using office BP measurements.